Peningkatan Pengetahuan Higiene Sanitasi di Depot Air Minum: Studi Kasus Pelatihan di Puskesmas Rumbai Bukit - Herniwanti, Herniwanti; Dewi, Oktavia; Rany, Novita; Nashabila, Rafni (Yumary: Jurnal Pengabdian kepada Masyarakat, 2025)
Purpose: This study aims to enhance hygiene and sanitation knowledge among drinking water depot operators in the working area of Rumbai Bukit Public Health Center, Pekanbaru. Through the training conducted, participants are expected to meet the requirements to obtain hygiene sanitation certificates from the Health Department. Methodology: The methodology employed is a collaborative approach, where drinking water depot operators are invited to participate in training that includes both theory and practice of sanitation. This training involves experts from the local Public Health Center at Puskesmas Rumbai Bukit. Results: The results indicate that the training was attended by 90% of the invited operators, with an average pre-training evaluation score of 60%, which increased to 78% post-training, reflecting a 21% improvement in knowledge. Conclusions: The training on sanitation hygiene in drinking water depots conducted at Puskesmas Rumbai Bukit, Pekanbaru, proved effective in improving participants’ understanding, as seen from the increase in the average score from 60% (pre-test) to 78% (post-test). The high participation rate (90%) indicates the community’s enthusiasm and need for increased knowledge in this area. Limitations: However, there are challenges in participation due to the self-funded nature of the training and some operators considering the certification process too complicated. Contribution: The contribution of this research is expected to provide recommendations for raising awareness of the importance of hygiene sanitation in drinking water depots and to support public health policies. Thus, this activity not only benefits the participants but also the wider community through the provision of safer and higher-quality drinking water.